Vitamin A deficiency Disorders among the Rural Pre-School Children of South India - Arlappa Nimmathota; Balakrishna Nagalla; Laxmaiah Avula; Brahmam GNV (International Journal of Nutrition, 2016)
Objectives: Vitamin A deficiency (VAD) among the rural pre-school children in India is continues to be a major nutritional problem of public health significance, even after the implementation of national vitamin A prophylaxis programme for more than four decades. The aim of the study was to assess the prevalence of vitamin A deficiency among rural pre-school children of South India. Methodology: A community based cross-section study; adopting multi-stage random sampling procedure was carried out by the National Nutrition Monitoring Bureau (NNMB) among rural pre-school children of four South Indian states viz. Kerala, Tamil Nadu, Andhra Pradesh and Karnataka during 2003-05. A total of 35,480 (Boys: 18,216; Girls: 17,264) rural children of 1-5 year age group was covered for this study. Key Results: The prevalence of Bitot’s spot, an objective ocular sign of VAD among the rural pre-school children of South Indian was 0.6% (95%CI:0.5-0.7). Similarly, the proportion of children with sub-clinical VAD was 59.3%, suggestive of a severe public health problem. In general, the prevalence of VAD was significantly higher (p<0.001) among the children of socio-economically marginalized sections of the communities, labourers, illiterate mothers and those residing in the households with no sanitary latrine. Conclusion: The prevalence of clinical and sub-clinical VAD among the rural pre-school children of south India is suggestive of a public health concern. Therefore, rural communities are encouraged to consume diets rich in pre-formed and pro-vitamin A and administer periodic massive dose vitamin A solution to the children of under five for the prevention and control of VAD.
Keywords: Vitamin A deficiency